Cremastra saprophytica (Orchidaceae: Epidendroideae), a new leafless autonomously self-pollinating orchid species from Gifu Prefecture, Japan - Suetsugu, Kenji (Phytotaxa, 2021)
A new species of Cremastra (Orchidaceae), C. saprophytica, is described from Gifu Prefecture, Japan. The new species is similar to C. aphylla in having a leafless and mycoheterotrophic habit. However, it is distinguishable from C. aphylla by its green stem, more closed perianth tube, smaller lateral lobes of lip, smaller callus of lip positioned at base of the midlobe and absence of a rostellum and viscidium. An illustration and ecological information on the new species are provided. A key to the Cremastra species is also provided.